The girl at midnight - Grey, Melissa (Grey, Melissa. Girl at midnight series., 2015)
"A girl, who's adopted and raised by a race of creatures with feathers for hair and magic in their veins, becomes involved in an ancient war and a centuries-old love, discovering startling truths about the world she lives in"--